Uso do pedômetro como estratégia de promoção da atividade física e alteração nos componentes da síndrome metabólica em pessoas idosas - PINTO , Lélia Lessa Teixeira (2014)
The growth in the proportion of elderly people in Brazil in relation to other age groups has been most representative in recent decades and, concomitantly to that population aging there is the increased prevalence of chronic diseases, such as the metabolic syndrome. Whereas the metabolic syndrome is negatively influenced by improper lifestyle, new intervention strategies are relevant in order to promote the expansion of physical activity level and positive changes in the metabolic syndrome in the elderly. Thus, this study aimed to describe the methods of intervention using pedometer as a motivational strategy and the impact on the level of physical activity, and analyze the effectiveness of the use of pedometers in promoting changes in the components of the metabolic syndrome in older women. Quasi-experimental study in the city of Uberaba, Minas Gerais, Brazil. The sample was selected by convenience, consisted of 62 women Registration System, and Monitoring Hypertensive, and Diabetics in the city. The elderly women were allocated to the intervention and control groups. The study participants were submitted before and after twelve weeks to an individual interview guide containing sociodemographic information, health and behavioral, and anthropometric measurements (weight, height, waist circumference), blood pressure measurement and biochemical evaluations (triglycerides, HDL-cholesterol, total cholesterol and fasting glucose). Participants in the intervention group followed protocol with the use of concomitant daily pedometer to motivational strategies (phone calls, visits monthly, and flyer). Data analysis procedure was used descriptive statistics (absolute and relative frequency, mean and standard deviation) and inferential (Chi-square test, Student's t test for independent samples and ANOVA for repeated measures). The intervention performed showed a low reactivity and after the twelve week period using the pedometer was increased number of steps / day, reduced levels of fasting plasma glucose, triglycerides and total cholesterol. The intervention proved to be the potential to be applied in primary health care targeted to the elderly public.